Antecedents, outcomes and controls of staff turnover in selected hotels in Malaysia - A. Maniam, Vikineswaran (1999)
The research was carried out to obtain more information on the staff turnover scenario in the Malaysian lodging industry. To do this, four main areas related to staff turnover were studied. The areas are rate of turnover, antecedents or causes of turnover, outcomes of turnover and controls of turnover. The methodology used to gamer the required data and information was survey research technique, using a pre-tested questionnaire as the instrument. Response from seventy- nine hotels and resorts were analysed pertaining to the topic and the four areas. Detailed analysis of turnover rate showed that most hotels face an alarming rate of turnover. The average turnover rate of the sample is 9.97%, with hotels averaging at 9.80% and the resorts at 10.03%. Although the t-test showed no significant differences between hotels and resorts, the higher turnover rate in resorts is due to the nature of business requiring more staff per room. The expansion of resorts was too fast in a tight labour market situation, rendering mass employment of foreign labour on a contract basis. The fluctuating nature of the hospitality business was not in favour of staff retention and together with other factors such as individual work related variables and availability of alternate jobs became antecedents to high staff turnover. Similar causes were also true for hotels.